Micro-credentials and Lifelong Learning in Higher Education: Italian and Kazakh regulatory frameworks - Lantero, L.; Finocchietti, Ch.; Kulumzhanova, A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
Micro-credentials have gained attention in public policies over the last few years. This paper, the scope of which is on micro-credentials in higher education with a particular focus on the European and Asian perspective, will explore the key policy documents in the European context, some of the available evidence, and the link between Higher Education, training, labour market and micro-credentials in the analysis of two national case studies in Italy and Kazakhstan.